Kajian Unsur Kebudayaan Indonesia dalam Novel Bumi Karya Tere Liye - Rohma, Marisa Nur; Dzarna, Dzarna; Anggraeni, Astri Widyaruli (ppjbsip, 2025)
This study aims to examine elements of Indonesian culture in Tere Liye's novel Bumi using a literary anthropology approach. The analysis is based on Koentjaraningrat's seven dimensions of culture theory, which includes social organization systems, religious systems and ceremonies, livelihood systems, knowledge systems, technology and equipment systems, language systems, and arts. The research method used is descriptive qualitative with documentation techniques and data analysis through reduction, presentation, and conclusion drawing. The results show that the novel Bumi represents six of the seven dimensions of culture, namely social organization, religion, livelihood, science, technology and equipment, and language. The element of art is not explicitly found in the text. These findings prove that the novel Bumi not only has aesthetic value as a work of literature, but also serves as a medium for the preservation, internalization, and reflection of the culture of the archipelago. This study is expected to enrich culture-based literary studies while contributing to the learning of Indonesian language and literature. AbstrakPenelitian ini bertujuan untuk mengkaji unsur-unsur kebudayaan Indonesia dalam novel Bumi karya Tere Liye dengan menggunakan pendekatan antropologi sastra. Analisis didasarkan pada teori tujuh dimensi kebudayaan Koentjaraningrat, yang meliputi sistem organisasi sosial, sistem religi dan upacara keagamaan, sistem mata pencaharian, sistem ilmu pengetahuan, sistem teknologi dan peralatan, sistem bahasa, serta kesenian. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik dokumentasi dan analisis data melalui reduksi, penyajian, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa novel Bumi merepresentasikan enam dari tujuh dimensi kebudayaan, yakni sistem organisasi sosial, religi, mata pencaharian, ilmu pengetahuan, teknologi dan peralatan, serta bahasa. Adapun unsur kesenian tidak ditemukan secara eksplisit dalam teks. Temuan ini membuktikan bahwa novel Bumi tidak hanya memiliki nilai estetika sebagai karya sastra, tetapi juga berperan sebagai media pelestarian, internalisasi, dan refleksi budaya Nusantara. Penelitian ini diharapkan dapat memperkaya kajian sastra berbasis budaya sekaligus memberikan kontribusi dalam pembelajaran bahasa dan sastra Indonesia.